Confined Co9S8 into a defective carbon matrix as a bifunctional oxygen electrocatalyst for rechargeable zinc–air batteries. Issue 20 (30th September 2019) - Meng, Lu; Zhan, Ling; Jiang, Hongliang; Zhu, Yihua; Li, Chunzhong
Abstract : CE-Co9 S8 @N, S-CM shows remarkable performance as a bi-functional electrocatalyst, and shows potential in the practical application of zinc–air batteries. Abstract : Porous nanostructures with high specific surface area and small-sized nanoparticles always exhibit an extraordinary electrochemical catalysis. In this study, we report an efficient method to obtain size-controllable Co9 S8 derived from metal organic frameworks (MOFs) as a bi-functional catalyst. The particle size of Co9 S8 could be finely controlled by tuning the Zn/Co molar ratios in the precursors. The obtained material exhibited optimal performance towards oxygen reactions and zinc–air batteries. The prominent electrochemical properties are mainly ascribed to the synergistic effect of small-sized Co9 S8 and the heteroatom-doped carbon matrix.